2014
DOI: 10.1016/j.epsl.2013.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Dating the Homo erectus bearing travertine from Kocabaş (Denizli, Turkey) at at least 1.1 Ma

Abstract: cited By 20International audienceno abstrac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(70 citation statements)
references
References 38 publications
5
63
0
2
Order By: Relevance
“…), dissolution Lopez et al (2017), Westaway (1993), Pentecost et al (1997), Kele et al (2011), De Filippis et al (2012, Özkul et al (2013), Van Noten et al (2013), Lebatard et al (2014), Claes et al (2015Claes et al ( , 2017aClaes et al ( , 2017b Sorey and Colvard (1997), Fouke et al (2000Fouke et al ( , 2003, Kharaka et al (2000), Chafetz and Guidry (2003), Kandianis et al (2008), Veysey et al (2008) Cipriani et al (1977), Barazzuoli et al (1988), Guo and Riding (1992, Pentecost (1995), Minissale et al (2002), Brogi et al (2007), Brogi and Capezzuoli (2008), Pedley (2009), Gandin and Capezzuoli (2014) Arp et al (2001Arp et al ( , 2010, Shiraishi et al (2008aShiraishi et al ( , 2008b, Brinkmann et al (2015) (continued on next page) et al, 2012; Nielsen et al, 2014). Lab and field studies report ACC phases found in close association with crystalline CaCO 3 (Jones and Peng, 2012a;Pedley, 2014) and/or organisms (cyanobacteria) or organic substances (Couradeau et al, 2012;Benzerara et al, 2014;Martignier et al, 2017).…”
Section: Tablementioning
confidence: 99%
“…), dissolution Lopez et al (2017), Westaway (1993), Pentecost et al (1997), Kele et al (2011), De Filippis et al (2012, Özkul et al (2013), Van Noten et al (2013), Lebatard et al (2014), Claes et al (2015Claes et al ( , 2017aClaes et al ( , 2017b Sorey and Colvard (1997), Fouke et al (2000Fouke et al ( , 2003, Kharaka et al (2000), Chafetz and Guidry (2003), Kandianis et al (2008), Veysey et al (2008) Cipriani et al (1977), Barazzuoli et al (1988), Guo and Riding (1992, Pentecost (1995), Minissale et al (2002), Brogi et al (2007), Brogi and Capezzuoli (2008), Pedley (2009), Gandin and Capezzuoli (2014) Arp et al (2001Arp et al ( , 2010, Shiraishi et al (2008aShiraishi et al ( , 2008b, Brinkmann et al (2015) (continued on next page) et al, 2012; Nielsen et al, 2014). Lab and field studies report ACC phases found in close association with crystalline CaCO 3 (Jones and Peng, 2012a;Pedley, 2014) and/or organisms (cyanobacteria) or organic substances (Couradeau et al, 2012;Benzerara et al, 2014;Martignier et al, 2017).…”
Section: Tablementioning
confidence: 99%
“…A multidisciplinary study combining sedimentological, paleontological, and paleoanthropological observations was performed by Lebatard et al (2014), who provided Karakoçan an absolute chronological framework for the upper fossiliferous travertine unit where the Kocabaş hominid and fauna were discovered at the Denizli-Kocabaş travertine. The paper constrained the minimum age of 1.1 Ma for the end of massive travertine deposition.…”
mentioning
confidence: 99%
“…Our investigation of the Early Pleistocene sequence has already yielded a significant chance find of an early hominin artefact . Taken in the context of the latest age determination of the hominin remains from nearby Kocabaş (Lebatard et al, 2014), these observations underline the probable significance of Western Anatolia as a dispersal route for early hominins. Could the Gediz fluvial archive provide the stratigraphical framework for deciphering this Palaeolithic archive?…”
Section: Discussion and Identification Of Priorities For Future Workmentioning
confidence: 70%